A switchable absolute bandwidth tunable filter with etched slot. Issue 14 (22nd September 2018) - Shu, Jiao; Cheng, Chonghu; Ge, Chuan; Zhang, Yerong
Abstract: In this paper, a reconfigurable filter with tunable center-frequency and switchable bandwidths is proposed. Frequency flexibility is achieved by varactors in the inner resonant parts. The switchable bandwidth states are implemented by pin diode connected with the etched slot on the ground. The coupling coefficient could be adjusted by the physical size of grounded slot, which would determine filter's bandwidth. To demonstrate the scheme, a proof-of-concept prototype filter is designed at 800 MHz. The measurement results show the center frequency of the designed filter could be tuned from 720 to 820 MHz; meanwhile, the two states switches the passband bandwidth from 45 to 36 MHz via turning on/off the grounded pin diode. The proposed filter has been fabricated, and measured, and exhibits excellent performance.